Analisis Kelayakan Usahatani Sorgum (Sorghum.L) (Studi Kasus di Kelompok Wanita Tani (KWT) Pantes Desa Kebonpedes Kecamatan Kebonpedes Kabupaten Sukabumi) - Muhamad Restu Nugraha; Amalia Nur Milla; Neneng Kartika Rini (Paspalum: Jurnal Ilmiah Pertanian, 2022)
The study "Feasibility Analysis of Sorghum Farming is a case study conducted on the Women Farmers Group in Kebonpedes Village, Kebonpedes District, Sukabumi Regency". The problem formulation of this research is to find out how to analyze the feasibility of sorghum farming in Kebopedes Village. , Kebonpedes District, Sukabumi Regency. The purpose of this study was to determine how the analysis of sorghum farming in Kebonpedes Village, Kebonpedes District, Sukabumi Regency. This research method uses descriptive quantitative method. secondary information The sampling method in this study used purposive inspecting. The result of this study is an analysis of the feasibility of sorghum farming in female farmer groups in Kebonpedes Village, Kebonpedes District, seen from the results of BEP Prices and R/C that are feasible to do. Based on the information, it is known that the R/C value of all out farming costs is worth more than one. The R/C value for the absolute cost of sorghum cultivation is 9.380. Based on the R/C value of all farm costs obtained, sorghum has a very high R/C value of 4.55.